Evidence of Müller Glia Conversion Into Retina Ganglion Cells Using Neurogenin2 - Guimarães, Roberta Pereira de Melo; Landeira, Bruna Soares; Coelho, Diego Marques; Golbert, Daiane Cristina Ferreira; Silveira, Mariana S.; Linden, Rafael; de Melo Reis, Ricardo A.; Costa, Marcos R. (Frontiers in Cellular Neuroscience, 2018)
Degenerative retinopathies are the leading causes of irreversible visual impairment in the elderly, affecting hundreds of millions of patients. Müller glia cells (MGC), the main type of glia found in the vertebrate retina, can resume proliferation in the rodent adult injured retina but contribute weakly to tissue repair when compared to zebrafish retina. However, postnatal and adult mouse MGC can be genetically reprogrammed through the expression of the transcription factor (TF) Achaete-scute homolog 1 (ASCL1) into induced neurons (iNs), displaying key hallmarks of photoreceptors, bipolar and amacrine cells, which may contribute to regenerate the damaged retina. Here, we show that the TF neurogenin 2 (NEUROG2) is also sufficient to lineage-reprogram postnatal mouse MGC into iNs. The efficiency of MGC lineage conversion by NEUROG2 is similar to that observed after expression of ASCL1 and both TFs induce the generation of functionally active iNs. Treatment of MGC cultures with EGF and FGF2 prior to Neurog2 or Ascl1 expression enhances reprogramming efficiencies, what can be at least partially explained by an increase in the frequency of MGCs expressing sex determining region Y (SRY)-box 2 (SOX2). Transduction of either Neurog2 or Ascl1 led to the upregulation of key retina neuronal genes in MGC-derived iNs, but only NEUROG2 induced a consistent increase in the expression of putative retinal ganglion cell (RGC) genes. Moreover, in vivo electroporation of Neurog2 in late progenitors from the neonatal rat retina, which are transcriptionally similar to MGCs, also induced a shift in the generation of retinal cell subtypes, favoring neuronal differentiation at the expense of MGCs and resuming the generation of RGCs. Altogether, our data indicate that NEUROG2 induces lineage conversion of postnatal rodent MGCs into RGC-like iNs in vitro and resumes the generation of this neuronal type from late progenitors of the retina in vivo.